Community Empowerment in the Development of Bayan Tourism Villages in North Lombok District - ASTITI, Anak Agung Eka Putri Dewi; MERTHA, I Wayan; KENCANA, I Putu Eka Nila (PT Keberlanjutan Strategis Indonesia, 2024)
Community empowerment is an important aspect in developing tourist villages. This is because the development of tourist villages uses a lot of resources owned by the community. The community has an important role in supporting the success of tourism village development so that powerless communities need to be empowered to create independence and economic prosperity for the community. This type of research is qualitative research using data collection techniques, namely interviews, documentation, observation, focus group discussions and literature studies. Interviews are a data collection method with both direct and indirect data sources. This study examines tourism potential, the role of the community and how to empower the community. Data sources were obtained from the head of Bayan Village, the head of the tourism awareness group, traditional leaders of Bayan Village and the community in Bayan Village to serve as sources. The village can be used as a tourist attraction so that it can invite tourists to come to the Bayan Tourism Village. The existence of this tourist village can increase income opportunities for the community and reduce unemployment. Empowerment is carried out by providing training to the Bayan village community about tourism so that they can take advantage of the opportunities that exist in the Bayan tourist village and can create their own employment opportunities. Having a tourist village can empower the community in Bayan Village, North Lombok Regency.